GAMBARAN PENGETAHUAN DAN SIKAP TERKAIT VULVA HYGIENE PADA REMAJA WANITA DIRW 02 BOJONG MENTENG, BEKASI - Irfani Rizqi Dwi Arifiani (2020)
Vulva Hygiene is a maintaining or maintaining the cleanliness of the external genital organs. The benefits of vulva hygiene are to keep the vagina clean, comfortable while on the move and to avoid vaginal discharge problems. This research was conducted to identify the description of knowledge and attitudes. This research uses descriptive research method, with a research population of adolescents living in RW 02 Bojong Menteng, Bekasi. The sampling method used was purposive sampling. Data collection methods used are questionnaires, interviews and institutions or institutions that support research. Data analysis used is univariate analysis. 109 respondents, the majority of respondents aged 19-24 years, had sufficient knowledge about vulva hygiene and had an attitude about good vulva hygiene. 109 female adolescent respondents who live in RW 02 Bojong Menteng, Bekasi are 72 to 24 years old, Female adolescents who live in RW 02 Bojong Menteng, Bekasi have sufficient knowledge about vulva hygiene as many as 53 respondents or 48.7% and have a good attitude about vulva hygiene as many as 76 respondents or 69.7%. Most of the young women who are in bojong menteng, Bekasi have a sufficient level of knowledge and good attitude.